'Who does this patient belong to?' boundary work and the re/making of (NSTEMI) heart attack patients. Issue 8 (28th June 2018) - Cramer, Helen; Hughes, Jacki; Johnson, Rachel; Evans, Maggie; Deaton, Christi; Timmis, Adam; Hemingway, Harry; Feder, Gene; Featherstone, Katie
Abstract: This ethnography within ten English and Welsh hospitals explores the significance of boundary work and the impacts of this work on the quality of care experienced by heart attack patients who have suspected non‐ST segment elevation myocardial infarction (NSTEMI) /non‐ST elevation acute coronary syndrome. Beginning with the initial identification and prioritisation of patients, boundary work informed negotiations over responsibility for patients, their transfer and admission to different wards, and their access to specific domains in order to receive diagnostic tests and treatment. In order to navigate boundaries successfully and for their clinical needs to be more easily recognised by staff, a patient needed to become a stable boundary object. Ongoing uncertainty in fixing their clinical classification, was a key reason why many NSTEMI patients faltered as boundary objects. Viewing NSTEMI patients as boundary objects helps to articulate the critical and ongoing process of classification and categorisation in the creation and maintenance of boundary objects. We show the essential, but hidden, role of boundary actors in making and re‐making patients into boundary objects. Physical location was critical and the parallel processes of exclusion and restriction of boundary object status can lead to marginalisation of some patients and inequalities of care (A virtual abstract of this paper can be viewed at:https://www.youtube.com/channel/UC_979cmCmR9rLrKuD7z0ycA ).